Variations in activity of Ru/TiO(2 )and Ru/Al2O3 catalysts for CO2 hydrogenation: an investigation by in-situ infrared spectroscopy studies - Dongapure, Pavan; Bagchi, Sayan; Mayadevi, S.; Devi, R. Nandini (Molecular Catalysis, 2020)
CO2 hydrogenation to methane, an important reaction strategically and also for value adding to CO2, is investigated on two different catalysts, Ru supported on alumina as well as titania to understand better low temperature activity of Ru/TiO2 catalyst. In-situ infrared studies are carried out in three different steps, viz., (i) CO2 adsorption on fully reduced catalyst (ii) reaction of these adsorbed species with gaseous H-2 and (iii) under co-feed of CO2 and H-2, at different temperatures. On Ru/Al2O3 catalyst, CO2 reacts with hydroxyls on the support surface to form carbonate and adsorbs reductively on metal as CO. Further reduction to formate and methyl species occurs on reaction with H. Small concentration of the reactive intermediate formyl forms only at high temperatures. Whereas, bare TiO2 itself seems capable of reductive adsorption of CO2 as formate indicating enhanced reducibility of titania based catalyst. Formyl groups are observed at low temperatures in Ru/TiO2 in step (ii), which further forms methyl and gaseous methane at much lower temperatures when compared to alumina catalyst. Highly reactive CO species loosely bound to metal-support interface observed at high temperatures, which is not present on Ru/Al2O3 catalyst also makes this catalyst superior. In comparison, linearly bound CO seen in alumina catalyst is not as reactive.
Keywords: CO2 hydrogenation; In-situ infra red spectroscopy; Ru/Al2O3; Ru/TiO2